Strategi Efektif dalam Manajemen Sumber Daya Manusia untuk Meningkatkan Produktivitas Perusahaan - Salsabilla, Nadiva (CV. Dalle’ Deceng Abeeayla, 2025)
This study aims to identify and analyze HRM management strategies that can improve employee performance and support the achievement of company goals. The research method used is a qualitative approach with case studies in several companies that implement performance-based HRM strategies. Data collection was carried out through in-depth interviews with HRM managers, direct observation of employee management practices, and analysis of company documents related to HRM policies. The results of the study indicate that strategies that focus on developing employee competencies, implementing a fair reward system, and establishing a collaborative work culture can significantly increase employee motivation and productivity. This study contributes by providing recommendations for companies in designing HRM policies that are more adaptive to changes in the business environment and employee needs. By understanding effective HRM management strategies, companies can create a more conducive work environment, increase employee loyalty, and encourage sustainable business growth. The results of this study are expected to be a reference for academics and practitioners in developing more innovative and strategic HRM management practices to face business challenges in the modern era.